STUDENTS’ OPINIONS TOWARDS PLACE-BASED EDUCATION APPROACH IN SCIENCE EDUCATION: A CASE STUDY - Ahmet Volkan YÜZÜAK; Zeynep Alemdar ZIHNI (MOJES: Malaysian Online Journal of Educational Sciences, 2022)
The aim of this study is to state the views of students on place-based education in science education. For this reason, it was primarily tried to establish the perspectives of the students against nature. It has been tried to show how their proximity to nature and their immediate environment affects their view of place-based education. This research is a qualitative study and was conducted in 2019-2020 academic year. Six volunteer students participated in the study. Semi-structured interviews were used for the data collection tools. The study was implemented to 6 students who attending elementary school in Turkey. Results of the study revealed the relation between the science education and nature. Even though the students accepted that the science course and nature are in a close relationship with each other, but activities in nature were not related to science lecture. Additionally, it was determined that although they lived in an environment that is rich in natural beauty, they did not have adequate information related to their environment. The study also showed that the student are very interested in outdoor activities but they cannot relate those activities to the science education. Considering all these findings, new studies can reveal how beneficial place-based education is for science lessons by having students do outdoor activities. Because it is seen in the research results those students may be interested in different learning environments. In addition, after the activities to be done, students the level of linking between science lessons and out-of-school practices can be looked at. Also, one of the studies that can be done is to examine the change in their interest towards the place where they live as they get to know their close environment.